Analysis of Air Shot Blasting Machine Effectiveness using Overall Equipment Effectiveness (OEE) - Setiawan, Ah. Andi; Saifuddin, Joumil Aidin (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
The effectiveness of a machine is one of the main factors for a production process to run smoothly so that it can meet its demand. Companies must always ensure that their production machines have high effectiveness. The shot blasting machine is one of the production machines used at PT. X. This machine has been in use for quite some time. Additionally, the machine often experiences breakdowns. This study was conducted to measure the effectiveness of the shot blasting machine at PT. X in order to determine its effectiveness. The overall equipment effectiveness (OEE) approach is used here to measure it. The OEE value is influenced by three factors, namely availability, performance, and quality. The result obtained is that the effectiveness of the machine is still quite high, with an OEE value of 81.82% and is still above the standard value for OEE, which is 85%. To enhance OEE, additional steps could involve documenting the issues as they arise, followed by generating a pareto chart to pinpoint the most common problems. This enables directing improvement endeavors towards addressing these significant challenges